The politics and teacher education programs: a critical analysis - Luque Calienes, Patricia (2011)
This article has been elaborated with the purpose of revising the teaching formation in service of the public school teachers, especially in Peru, helping to understand the teaching formation itself as a complex phenomenon, with multiple sides. The process of creation of the educational policies must be in accordance with plans that come after them. The politics and the programs of training argue, among their objectives, the possibility of transforming the practice in something better, the article analyzes the process to achieve the transformation. Additionally, a brief presentation of the program of teaching formation, implemented by the Ministry of Education in 2002, is shown.